CONSTRUCTION AND VALIDATION OF A CLINICAL SIMULATION SCENARIO FOR TEACHING CONFLICT MANAGEMENT - Lima, Lucas Garcia; Draganov, Patricia Bover; Sampietri, Igor Cintra; Saito, Katya Araújo Machado; Balsanelli, Alexandre Pazetto (Cogitare Enfermagem, 2023)
Objective: Develop and validate a clinical simulation scenario for undergrad nursing students to learn conflict management. Method: Methodological study in which a conflict management scenario was constructed in the city of São Paulo, SP, Brazil, in 2022, based on the literature review and the pedagogical experience of the researchers. Content validation was carried out with judges in the field using the Delphi technique. The data was analyzed with a Content Validity Index (CVI>80%). Results: The scenario describes the scene of a nursing trainee asking the nursing technician to bathe a patient in bed. This is permeated by interpersonal conflicts. The content validation involved eight experts in clinical simulation and two nursing students. There were three "rounds," reaching IVC 100%. Conclusion: The scenario was validated and will contribute to the practical teaching of this skill in undergraduate courses.